Notice of Removal: Short-term load forecasting methods: A review - Srivastava A.K.; Pandey A.S.; Singh D. (My University, 2025)
For decision makers in the electricity sector, the decision process is complex with several different levels that have to be taken into consideration. These comprise for instance the planning of facilities and an optimal day-to-day operation of the power plant. These decisions address widely different time-horizons and aspects of the system. For accomplishing these tasks load forecasts are very important. This paper presents a comprehensive survey of the short term load forecasting. It also reviews various methodologies for short term load forecasting (STLF). Authors strongly believe that this survey article shall be very much helpful to the researchers working in the field of short term load forecasting for finding out the appropriate references and future work. © 2016 IEEE.